The Role Of Folk Medicine In The Life Of Peoples Central Asia - G. Muminova; O. Ochilova (Euro Asian Journal Publishing, 2024)
Central Asia occupies a unique place in world civilization as a region where medicine has developed since ancient times. This land has nurtured great figures and thinkers in medical science. Throughout their careers, medical experts used the experience of not only representatives of Central Asia, but also the experience of other peoples: Greeks, Persians, Arabs, Chinese, Indians.
Keywords: civilization; medicine; traditional medicine